Butyryl-cholinesterase deficiency: A case report of delayed recovery after general anaesthesia - Ahmed Al-Emam (Toxicology Reports, 2021)
Background: Apnoea and prolonged paralysis after succinylcholine administration is not uncommon occurrence in anaesthetic practice. It occurs due to inherited or acquired deficiency of butyrylcholinesterase. Case report: Here we report a case of succinylcholine apnoea for 2 h in a 5 years old girl who was anaesthetized for bronchoscopic extraction of a foreign body. She was subsequently kept on assisted ventilation. She recovered few minutes after I.V. atropine and naloxone. Laboratory investigation revealed low cholinesterase activity. Thus the girl was given 150 mL fresh frozen plasma. She has been discharged the next day after complete recovery. Conclusion: As the genetic analysis was not available to confirm the diagnosis of atypical variant of cholinesterase. The family was advised to submit serum samples for assessment of cholinesterase activity and avoid exposure to cholinesterase inhibitors. Moreover, clear instructions were given to the family so they can warn the anaesthetists in case any family member undergoes general anesthesia for any reason in the future. Furthermore, they must be strongly advised to avoid exposure to anticholinesterases as they might have heightened sensitivity to these agents. It should be emphasized that Naloxone and atropine could help speed up recovery in such cases.